Horizon in a Simple Model of Economic Growth - Keeler, Emmett (Econometrica, 1974)
In long-run planning, targets may be set further in the future than economic technologies can be estimated. How costly in hindsight is limited foresight? Following Los, we say K is an e-horizon if knowledge of economic possibilities for the next K time periods permits decisions with results at most E worse than optimal. For a dynamic Leontief model, we show that any T-period efficient path is almost as big as all feasible T-period paths during the first T - K periods. Thus, given K periods notice, we can plan an E-optimal growth path no matter how technologies change after T.